Impulsive Buying Behavior Towards Livestream Shopping through S-O-R Framework: An Islamic Economic Perspective (Case Study of the Central Java Muslim Community) - Shofi Balqissafira Afna,; Marwini, (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
This study aims to analyze the factors that cause impulsive buying behavior towards livestream shopping through the Stimulus-Organism-Response (S-O-R) framework. Methods of data collection are done through a questionnaire. The research population includes the Muslim community of Central Java who have purchased products in livestream shopping with a sample of 220 respondents. The analysis tool used is SmartPLS 3.2.9 using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) analysis method. The results of the analysis show that the stimulus factors which include interpersonal interaction, discount vouchers, and flash sales have a positive and significant effect on the perceived enjoyment of livestream shopping in the Muslim community of Central Java. In addition, the stimulus factors in the form of purchase convenience, product usefulness, and product price also positively and significantly affect the perceived usefulness of livestream shopping in the Muslim community of Central Java. As for the variables which are organisms, including the perceived enjoyment of livestream shopping and the perceived usefulness of livestream shopping, both have a positive and significant effect on the impulsive buying behavior of the Muslim community in Central Java which is the response in this study.